THE AXIOLOGY OF PANCASILA IN THE RECONSTRUCTION OF LEGAL CULTURE IN INDONESIA - Junaedi Junaedi (UNIFIKASI : Jurnal Ilmu Hukum, 2019)
Pancasila is the result of a consensus with the founding fathers of the nation. Pancasila as a view of life and an ideology of the Unitary State of the Republic of Indonesia provides direction and goal to create an equitable and prosperous community. This study aims to analyze how the Axiology of Pancasila in the Reconstruction of Legal Culture in Indonesia. The method used in this study was normative juridical. The results showed that Pancasila is listed in the Preamble of the 1945 Constitution as a state constitution that needs to be actualized in daily life. Consequently, the values of Pancasila as a result of the crystallization of the nation’s culture that is multiculturalism must be reflected in the mindset, creativity, taste and behavior of Indonesian people. In the field of law, the values of Pancasila must be reflected in law enforcement with a sense of social justice for all Indonesian people. Hence, the legal culture characterized by the values of Pancasila needs to be actualized in order to realize national legal awareness in an effort to develop laws that protect and provide a sense of justice for all Indonesian people.Pancasila adalah hasil konsensus bersama para pendiri bangsa Indonesia. Pancasila sebagai ideologi dan pandangan hidup bangsa memberikan arah dan tujuan untuk membangun masyarakat Indonesia yang adil dan makmur dalam NKRI.  Tujuan penelitian ini adalah bagaimana Aksiologi Pancasila dalam Rekonstruksi Budaya Hukum Di Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif. Hasil penelitian yaitu Pancasila tercantum dalam Pembukaan UUD 1945 sebagai konsitusi Negara yang perlu diaktualisasikan dalam kehidupan sehari-hari. Sehingga memberikan konsekuensi, bahwa nilai-nilai Pancasila sebagai hasil kristalisasi budaya bangsa yang bersifat multikulturalisme harus tercermin dalam pola pikir, cipta rasa dan tingkah laku masyarakat Indonesia. Dalam bidang hukum, nilai-nilai Pancasila harus tercermin dalam penegakan hukum yang berwatak rasa keadilan sosial bagi seluruh rakyat Indonesia. Sehingga budaya hukum yang berkarakter nilai-nilai Pancasila perlu diaktualisasikan demi terwujudya kesadaran hukum nasional dalam upaya membangun hukum yang mengayomi dan memberikan rasa keadilan bagi seluruh rakyat Indonesia.